IN VITRO CULTURE OF ZYGOTIC EMBRYOS OF Syagrus romanzoffiana (CHAM.) GLASSMAN (ARECACEAE) - Kuroski Constantino, João Henrique; Ikeda, Angela Cristina; Sant'Anna-Santos, Bruno Francisco; Bomfim de Alcantara, Giovana (Floresta, 2025)
Syagrus romanzoffiana (Cham.) Glassman (Arecaceae) also known as queen palm, is a species of palm, widely distributed in Brazil. The queen palm is present in the food of animals and humans who consume both the fruit and the heart of palm. The species also has medicinal, ornamental and ecological importance. In vitro cultivation facilitates the germination of S. romanzoffiana, in which it is possible to obtain a high morphogenetic response. Thus, the objectives of the present work were to establish a protocol for the in vitro germination of S. romanzoffiana from the culture of zygotic embryos and to describe a methodology for the evaluation of the embryo viability with the use of tetrazolium. For this, fruits of S. romanzoffiana were collected, the embryos were excised and cultivated with dichlorophenoxyacetic acid (2,4-D) or gibberellic acid (GA3), in two experiments. In addition, the exposure time and concentration of tetrazolium were evaluated for embryo viability. The results showed that 39.4% of the embryos cultivated with 2,4-D and 25% cultivated with GA3 developed into seedlings. No significant difference in mass was found for seedlings developed with treatment with 2,4-D and GA3. In the tetrazolium test, 75% of the S. romanzoffiana embryos were considered viable. The in vitro germination protocol for S. romanzoffiana showed satisfactory germination results (32.2%) with only 27% contamination of the culture media.